Improvising with others. - Ryan, Joel (Contemporary Music Review, 2006)
This article presents an interview with computer-music composer Joel Ryan. He cites composer David Behrman as the inspiration for a number of composers to work with computers in music. He describes his approach to finding a meaningful music through the use of computers. Ryan also discusses his educational and career background.